Critical Thinking Education for Enhancing the Effectiveness of Education in Vietnam - Hang, Ngo Vu Thu (VNU Journal of Science: Education Research; Vol 34 No 1DO - 10.25073/2588-1159/vnuer.4122, 2018)
This paper presents basic theoretical knowledge of critical thinking. It describes characteristics of critical thinking, which are used for the formation of critical thinking indicators. These indicators are needed for assessing students’ critical thinking levels and for designing lessons to develop critical thinking competence for students. The paper articulates arguments for highlighting the necessity of critical thinking education for students in Vietnam. The paper contributes to knowledge base of critical thinking education and supports further studies on critical thinking in order to enhance the effectiveness of education in Vietnam.